PHILOSOPHICAL BASES OF DYNAMICS OF SCIENTIFIC THINKING - Vezirov, H.N; Vezirov-Kengerli, F.H (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
It is known that only philosophy can detect the incorrectness or inaccuracy of a scientific approach or research methodology, and show the possibility of improvement. At the same time, philosophy, relying on new scientific knowledge, enriches the content of well-known philosophical categories and opens up new ones. Any researcher of science, analyzing his results, sometimes even unconsciously, thinks and poses questions regarding the essence of the result obtained, about the relation of this result to other results and to the world in general. And even if he does not understand this, all the same, this reflection is philosophical in nature. A philosophical change in the dynamics of scientific thinking, which is the source of a radical transformation of both an individual person, humanity as a whole and life, and economic development, without which life is impossible in the modern world, clearly changes the dynamics of the impact of science on the pace of economic development, and science itself, and the pace and the direction of development of social progress in general. Understanding of scientific, philosophical and epistemological ideas allows you to more fully use the achievements of science for the benefit of mankind. And dialectical epistemology is a source of acceleration of the development of science. Understanding of science as something unshakable, permanent, unchangeable, i.e. non-dialectic - only an anchor and a brake on development. And in essence, epistemology implicitly, imperceptibly plays its role internal objective freedom. Today, freedom is the driving force behind the rapid and continuous change of theoretical scientific and, in particular, physical systems with the goal of striving to achieve ideal technologies. Approaching the ideal makes the development of mankind non-stop. The change and development of the theoretical ideals themselves leads to qualitative positive changes in science.